7 - Tribute to Professor Lansana Keita - CODESRIA, (CODESRIA Bulletin, 2025)
On June 5th 2024, the Council for the Development of Social Science Research in Africa (CODESRIA) received the news of the passing on of Prof. Lansana Keita. Prof. Keita’s intellectual contributions were profound and far-reaching, leaving an indelible mark in the ﬁelds of philosophy and economic history. His work has been a cherished part of CODESRIA’s programming and history, enriching our scholarly community in countless ways. His last publication with CODESRIA titled “Eurocentrism and the Contemporary Social Sciences” was published in Africa Development, Volume 45, No. 2, 2020 (https://doi.org/10.57054/ad.v45i2.641). The article is set to be republished in a forthcoming book edited by Wanjala S. Nasong’o and Eka Ikpe titled Beyond Disciplines: African Perspectives on Theory and Meth- od. In total, Prof. Keita contributed at least 11 articles to CODESRIA’s premier social science journal, Africa Development. He was also very creative in his engagement, including conducting interviews with well-known luminaries in his area of work. For instance, the article “The Economic Situation in Contemporary Africa” by Patrick Bond and Demba Moussa Dembele published in Africa Development Vol. 37, No. 4, 2012 is a comment on questions he posed.